Paradigmas en progressie in die teologie: "n Perspektief op die RGN-kongres van April 1988 - Merwe, P. J. van der (Hervormde teologiese studies, 1989)
Paradigms and progress in theology: A perspective on the HRSC conference of April 1988 The title refers to a conference believed to be the first interdisciplinary meeting on said theme in South Africa held under the auspices of the South African Human Sciences Research Council in Pretoria last year. Future developments in this field may prove it a major happening in South African theology and methodology yet. An anthology of selected papers read appeared from the press recently. This article contains a number of abstracts made from the book and brief discussions of papers thus abstracted. A basic hesitancy pertaining to the meaning and encompass of the concept ‘paradigm’ as well as a widespread uncertainty regarding theology’s accountability towards science are noted. Fears of dimensional reduction are expressed.